Comparison of topically applied flurbiprofen or bromfenac ophthalmic solution on post‐operative ocular hypertension in canine patients following cataract surgery. (18th March 2016) - Lu, Jennifer; English, Robert; Nadelstein, Brad; Weigt, Anne; Berdoulay, Andrew; Binder, Dan; Ngan, Esther
Abstract: Objective: To compare the prevalence and kinetics of ocular hypertension after routine cataract extraction when using a predominately COX‐2 inhibitor (bromfenac) versus a predominately COX‐1 inhibitor (flurbiprofen) in combination with a topical corticosteroid. Procedures: Patients undergoing unilateral or bilateral cataract surgery were randomly assigned to receive flurbiprofen or bromfenac at the day of surgery and continued for 6 weeks postoperatively, along with topical neo poly dexamethasone. No systemic nonsteroidal anti‐inflammatory medications were administered before or after surgery. Intraocular pressure was monitored pre and postoperatively. When an IOP of >25 mmHg was detected, therapeutic intervention was performed. Results: Eyes in both treatment groups showed a similar IOP profile with the highest mean IOP occurring two hours postsurgery and slowly declining during the next 6 weeks. However, eyes receiving bromfenac had a higher mean IOP at 2 h post‐op (22.1 mmHg) than eyes receiving flurbiprofen (18.8 mmHg) and a slower decrease in IOP in the weeks after surgery. Over the course of the study, a higher percentage of eyes receiving bromfenac had therapy discontinued over concerns of elevated IOP compared to eyes receiving flurbiprofen (bromfenac 23.1% and flurbiprofen 9.8%). On average, the risk of having elevated intraocular pressure with bromfenac is 1.04 times higher than with flurbiprofen. Conclusion: Elevated postoperative IOP was observed in both treatment groups; however, bromfenac‐treated eyes were more likely to require intervention for elevated IOP.